Combined Use of Negative Oral Contrast and Ranitidine for Magnetic Resonance Cholangiopancreatography: A Randomized Controlled Trial - Natarajan, Aravintho; Phansalkar, Dilip S.; Kurian, George; R., Mithun Raj; T., Preeth Pany; Jayabalan, Jayaranjeetham (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Objective Magnetic resonance cholangiopancreatography (MRCP) is a noninvasive imaging modality to study pancreaticobiliary tree. The primary aim of this study was to compare the image quality of MRCP obtained with the use of ferric ammonium chloride (negative oral contrast) with that of combined use of ferric ammonium chloride and ranitidine (administered orally). Secondary aim was to determine the interobserver agreement between the assessing radiologists.Materials and Methods The study was a single-center randomized-controlled trial. The patients were randomized into two groups. One group received ranitidine orally and ferric ammonium chloride (Dexorange) and the other group received only the ferric ammonium chloride. The images were qualitatively analyzed independently by the two blinded radiologists. Two scoring systems were used for grading the diagnostic quality of the images: the gastrointestinal tract signal intensity score (range: 1–4) and the structure visibility score (range: 0–3). The mean score of contrast effect and image effect of the two groups were compared by using Mann–Whitney U test. A p-value < 0.05 was considered statistically significant. Interobserver agreement was studied using Cohen kappa coefficient.Results A total of 93 patients were eligible for the study. Forty-one patients were randomly assigned to the group that received only negative oral contrast and 52 group that received both ranitidine and negative oral contrast. The mean score of the images obtained with using both ranitidine and negative oral contrast was significantly higher when compared with the other group (3.02 vs. 2.7) (p-value = 0.018). However, there was no significant difference in mean structure visualization score of various parts of the pancreaticobiliary system. The interobserver agreement between the two readers in our study was acceptable.Conclusion Combined use of hematinic syrup and ranitidine increases the image quality by improving the suppression of gastrointestinal fluid signal as compared with the use of only hematinic syrup as negative oral contrast.
Keywords: image quality; MRCP; negative oral contrast; ranitidine